Предмет: Алгебра,
автор: hun9ter
Упростите выражение
(3xy)^3 * (3x^-1 y)^-2 : (9x^3y^4)
Ответы
Автор ответа:
0
1) ( 3 x^-1 y ) ^ - 2 = ( 1/9 ) x^2 y^-2
2) ( 3 x y ) ^3 = 27 x^3 y^3
3) ( 1/9 ) х^2 y^-2 * 27 х^3 y^3 = 3 x^5 y
4) ( 3 x^5 y ) : ( 9x^3 y^4 ) = ( 1/3 ) x^2 y ^ - 3 = ( x^2 ) / ( 3 y^3
2) ( 3 x y ) ^3 = 27 x^3 y^3
3) ( 1/9 ) х^2 y^-2 * 27 х^3 y^3 = 3 x^5 y
4) ( 3 x^5 y ) : ( 9x^3 y^4 ) = ( 1/3 ) x^2 y ^ - 3 = ( x^2 ) / ( 3 y^3
Автор ответа:
0
А в задаче нет такого ответа
Похожие вопросы
Предмет: География,
автор: ssss7897
Предмет: Қазақ тiлi,
автор: erzat59
Предмет: Қазақ тiлi,
автор: amankeldyaiarusymbat
Предмет: Литература,
автор: angel1812
Предмет: Математика,
автор: vasilisa23